The Functioning of the Lexeme "Book" in Markus Zusak’s Novel "The Book Thief". - Semen, H; Hladkoskok, Lesia (Вісник Житомирського державного університету. Випуск 2 (88). Житомир, 2019)
The article deals with the usage of the lexeme ''book'' in Marcus Zusak’s novel ''The Book Thief''. The examples of contextual usage of the lexeme have been compared with the semantic structure of it fixed in the dictionary. The scientific methods of comparison and description have been used alongside distributional and contextual analysis in order to investigate the functioning of the lexeme ''book''. The role of the lexeme as the central concept of the novel is specified as well as its usage with different stylistic devices in the contexts with both positive and negative implications. The lexeme is used in combination with epithets, similes, hyperboles, personification and paradox. The accumulation of words related to the concept of book creates a specific effect in the text of the novel. Lexical meaning of a word is the realization of the concept, emotion or relation by certain means of language system. The definition, analysis and description of the connotations of the lexeme book is performed in the context and situations described in the novel. Reading and writing books can save life, improve character, give inspiration and at the same time they may be unnecessary and useless. It is proved that M. Zusak not being the eye-witness of the events created a novel of great aesthetic, educational and informative value, which needs explanation, discussion and investigation.
Keywords: word, meaning, lexico-semantic variant, lexeme, book.